Age-Dependent Impact of Medication Underuse and Strategies for Improvement - Meid, Andreas; Haefeli, Walter E. (Gerontology, 2016)
BACKGROUND: Medication underuse is common in aging populations and, because of the growing risk for competing deaths, the benefit of preventive medicines gradually vanishes with advancing age, thus limiting their success. - OBJECTIVE: To estimate the optimum time of initiation of the secondary prevention of cardiovascular events, we examined the impact of appropriate pharmacotherapy for different starting ages at which it is implemented. - METHODS: In the competing risk framework, we obtained the population's life course from life tables, combined it with effect estimates quantifying the real-world effectiveness of secondary prevention, and compared the outcome of patients not receiving appropriate treatment (underuse) with those receiving preventive medicines that have demonstrated a reduction in the transition to serious cardiovascular events (START criteria). Starting at the age of 55 years, the population proportions of the distinct states of the framework were calculated for each year of chronological age in subgroups of appropriate treatment and underuse. These proportions were used over a follow-up period to estimate measures of treatment effectiveness and risks of underuse. - RESULTS: Despite increasing relative effectiveness with advancing age, benefits measured by patient-relevant endpoints, such as life years gained (LYG) or gained quality-adjusted life years (QALYs), markedly dropped after the starting age of 75 years, but even at an initiation age of 85 years, QALYs gained exceeded 1 year. - CONCLUSION: Interventions targeting medication underuse may achieve considerable benefits at any stage of later life, while the benefit is probably largest if appropriate treatment is started before 75 years.
Gesehen am 06.05.2020